Optimizing Cryopreservation: The Effect of MitoTEMPO and Glycerol Ratios on Ram Semen Quality After Freezing and Thawing - Koca, Recep Hakki; Gungor, Ibrahim Halil; Cihangiroglu, Aslihan cakir; Acisu, Tutku Can; Badilli, Nida; Akarsu, Serkan Ali; Gur, Seyfettin (Wiley, 2025)
Background: MitoTEMPO is an important mitochondrial targeted and ROS scavenging antioxidant. It is often used as antiviral, anticancer and immunomodulator agents. In addition, there are studies proving its positive effect on sperm after thawing. Objectives: The aim of our study was to determine the effects of mitoTEMPO addition, which has strong antioxidant and cryoprotective properties in different glycerol ratios, on motility, kinematics, sperm quality and oxidative stress in spermatozoa after freezing and thawing. Materials and Methods: Semen was collected from seven rams twice a week for 3 weeks. The semen samples were pooled and extended using standard protocol. Experimental groups were formed (1 mu M mitoTEMPO with 3% glycerol, 1 mu M mitoTEMPO with 5% glycerol, 5 mu M mitoTEMPO with 3% glycerol and 5 mu M mitoTEMPO with 5% glycerol) and without (control with 3% glycerol and control with 5% glycerol) mitoTEMPO and they were frozen in mini straws. In this study, motility, kinematic parameters, plasma membrane integrity, mitochondrial membrane potential, acrosome integrity, viability, DNA fragmentation and oxidative stress parameters were determined. Results: The increases in total motility, increases in plasma membrane integrity ratio, decreases in MDA level and decreases in DNA damage ratio in mitoTEMPO groups were statistically significant (p < 0.05). Conclusion: Post-thawed sperm, the addition of 1 M mitoTEMPO to the 3% glycerol extender preserved the integrity of the spermatozoon membrane, increased total motility, prevented DNA damage and oxidative stress, and increased the rate of sperm with intact acrosome.
Keywords: cryopreservation; DNA fragmentation; mitoTEMPO; ram; semen